A residency style transition to practice program in trauma and critical care: The George Washington University Hospital experience. Issue 11 (8th November 2021) - Messing, Jonathan; Peters, Miranda; Vota, Amy; Seneff, Michael; Sarani, Babak
ABSTRACT: Transition to practice programs for nurse practitioners and physician assistants are gaining popularity and becoming more specialized. As these providers seek opportunities to strengthen their clinical skills and bridge the gap from school to practice, it is important to recognize the benefits and barriers of such programs. In this article, The George Washington University Hospital shares its experience in managing a transition to practice program for trauma and critical care.